DEVELOPMENT AS FREEDOM DAN PENCAPAIAN PERUBAHAN SOSIAL - Amril Maryolo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Social studies have many variations because society is not a single object. Social change is a phenomenon of community construction that has a variety of variations. Development is a word used to describe processes and efforts to enhance economic, political, cultural, social, and so on. With such an understanding